2015
DOI: 10.1016/j.urolonc.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors of malignancy and unfavorable pathology for clinical T1a tumors treated with partial nephrectomy: A multi-institutional analysis

Abstract: Purpose To determine preoperative predictors associated with RCC and unfavorable pathology in small renal masses treated with partial nephrectomy (PN). Materials and Methods PN records from 5 centers were retrospectively queried for patients with a clinically localized, single tumor < 4 cm on imaging (cT1a). Between 2007 and 2013, 1009 patients met inclusion criteria. Unfavorable pathology was defined as any grade III or IV RCC or tumors upstaged to pathologic T3a disease. Logistic regression models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 25 publications
(32 reference statements)
1
28
0
1
Order By: Relevance
“…Recent research has shown that higher tumour complexity (nephrometry score ≥8) is an independent predictor of unfavourable RCC pathology, i.e. high‐grade or pT3 disease . Therefore, it is possible that increased PN use for higher complexity tumours, as reported in the literature, has contributed to this trend .…”
Section: Discussionmentioning
confidence: 97%
“…Recent research has shown that higher tumour complexity (nephrometry score ≥8) is an independent predictor of unfavourable RCC pathology, i.e. high‐grade or pT3 disease . Therefore, it is possible that increased PN use for higher complexity tumours, as reported in the literature, has contributed to this trend .…”
Section: Discussionmentioning
confidence: 97%
“…The only finding that would push such a patient to intervention is PRB identification of high-grade or sarcomatoid RCC, which is not reliably detected, will likely exhibit a rapid GR and trigger subsequent intervention, and may not impact OS. We do recommend PRB for two distinct groups of patients: (1) those with intermediate risk of competing illness and progression of disease, for whom more information may help in making a decision regarding PI or AS; and (2) those with a high likelihood of benign disease (young women with tumors 3 cm) [22][23][24]. It E U R O P E A N U R O L O G Y X X X ( 2 0 1 5 ) X X X -X X X should be recognized that PRB may provide important tissue and identify benign lesions for a clearer understanding of oncologic outcomes in the AS cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Our center is increasingly integrating clinical data, 22 with renal mass biopsy 23 and nuclear imaging data, 24 to better determine which patients may be spared from surgical resection. However, for many patients in this 12-year series, these methods were unavailable or infrequently used at the time of their diagnosis.…”
Section: Discussionmentioning
confidence: 99%